Experimental Study on Shear Failure Characteristics of Jointed Rock Mass Based on Direct Shear Tests and Digital Image Correction Techniques. (21st January 2021) - Ren, Fenhua; Zhang, Liwei; Wu, Xinghui; Liu, Wensheng
Abstract : The instability of rock engineering is normally dominated by the shear failure of rock mass. The dip angle of discontinuous planes widely existing in rock mass is a key parameter affecting the shear strength and failure mode of jointed rock. This paper aims to investigate the influence of discontinuous joints on the shear failure of rock. Direct shear tests are carried out on rock-like specimens with discontinuous joints in different dip angles. During the shear tests, the strain field is monitored in real-time by digital image correction (DIC) technology. Experimental results show that the shear strength, shear strain evolution, and failure mode for the jointed specimens are affected by the dip angles of the discontinuous joints. The maximum shear strain of specimens with joint angles of 45° and 75° increases gradually with the increase of shear loading. The maximum shear strain for the specimens with joint angles of 0°, 15°, 30°, 60°, and 90° increases sharply after the shear load reaches 80% of the peak load. When the joint inclination angle is less than 45°, the crack begins to expand from the joint tip and is interconnected to form a penetrating fracture. When the joint dip angle is greater than 45°, the cracks initiate at the joint tip and then propagate at different paths resulting in multistage shearing and crushing failure.